ARTERIAL THROMBOSIS IN A COVID-19 PATIENT - Osmani Loga, Arlinda; Shopova, Zhaklina; Bosilkovski, Mile; Vidinic, Ivan; Poposki, Kostadin; Aliji, Vjolca; Kerela, Coskun (Македонско лекарско друштво = Macedonian medical association/De Gruyter, 2022)
Arterial thrombosis is one of the complications descry bed in severe COVID-19. Our presented case had throm bosis of abdominal aorta and left renal artery despite prophylactic treatment with low molecular heparin - enoxaparine. Thrombotic lesions were defined with CT angiography. Treatment consisted of therapeutic doses of low molecular heparin and Bergman solution. After 42 day of hospital treatment, the patient was dischar ged and vascular surgeon consultations were performed. By presenting this case, we want to draw attention to the need for early diagnosis of this complication and to highlight the need for treatment with therapeutic doses of low molecular heparin in patients with severe Covid pneumonia or oxygen dependent patients and in risk for thrombosis.
АРТЕРИСКА ТРОМБОЗА КАЈ ПАЦИЕНТ СО КОВИД 19
Keywords: COVID-19; arterial thrombosis; heparin